Simple and multiple resistances to viruses in cowpea genotypes - Lima, José Albersio Araujo; da Silva, Ana Kelly Firmino; Aragão, Maria do Livramento; Ferreira, Nádia Rutielly de Araújo; Teófilo, Elizita Maria (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to identify new sources of simple and multiple resistances to Cowpea severe mosaic virus (CPSMV), Cowpea aphid-borne mosaic virus (CABMV) and Cucumber mosaic virus (CMV) isolates in cowpea (Vigna unguiculata). Thirty-three genotypes from the germplasm bank of Universidade Federal do Ceará were tested as to their resistance to four CPSMV isolates, two CABMV isolates and one CMV isolate. Twenty-five days after the first virus inoculations, all inoculated plants, including the asymptomatic ones, were tested by serology. Genotypes were classified as: immune, plants without symptoms and negative serology; resistant, plants with mild mosaic and positive serology; susceptible, plants with mosaic and positive serology; and highly susceptible, plants with severe mosaic, other systemic symptoms, including systemic necrosis, and positive serology. Simple and multiple resistances to viruses were identified among the evaluated genotypes, but none of them showed multiple immunities to all isolates. Four genotypes showed immunity to all CPSMV isolates, two were immune to CABMV and two showed immunity to CMV. Eleven genotypes showed multiple resistances to two viruses, allowing for the development of new cultivars with more stable and broader resistance. Genotypes Purple Knuckle Hull-55, MNC-03-731C-21 and CNCx284-66E show resistance to CABMV, even when inoculated with CMV.